AGING AND FUNCTIONAL COMPLEX ACTIVITIES: CLINICAL AND SOCIAL PERSPECTIVES - Edith, Labos; Karina, Zabala; Sofía, Trojanowski; Miriam, Del; Ana, Bento; Alejandro, Renato (PEOPLE: International Journal of Social Sciences, 2017)
Background: Several papers describe functional changes in the aging population, and its relevance in early detection.Objectives: In order to count on a tool to evaluate the performance in the use of new technologies we have designed a new protocol - Complex Functional Study (CFS)-that quantifies performance and functional changes related to previous states.Our objectives are to study the aging population with this lately developed tool.Methods: We evaluated 350 healthy subjects grouped according to age and instruction levels. We administered a General Cognitive Screening and the CFS. We used ANOVA Test, and Regression Analysis and Principal Components.Results: Our finding verifies that the 15.75% registered functional loss and the 2.8%, registered changes in performance. The differences in the averages were higher at the age range 80-90. The measure of change proved to have less impact in groups with higher instruction level. A greater functional loss has been registered in older participants with less instruction level.Conclusions: This study enables the use of the CFS as a tool of clinical interest for the detection of incipient impairment in daily living complex functional skills.The results obtained verify a good performance in those skills in most of the studied population. On the other hand, this study has also a psycho-social perspective insofar as it fosters significant learning processes. In this way it will be possible to implement strategies to develop social awareness about the learning capacity in the elderly to impact in the social net and on their wellbeing.